Review for Retrospective Exposure Assessment Methods Used in Epidemiologic Cancer Risk Studies of Semiconductor Workers: Limitations and Recommendations - Donguk Park (Elsevier, 2018)
This article aims to provide a systematic review of the exposure assessment methods used to assign wafer fabrication (fab) workers in epidemiologic cohort studies of mortality from all causes and various cancers. Epidemiologic and exposure-assessment studies of silicon wafer fab operations in the semiconductor industry were collected through an extensive literature review of articles reported until 2017. The studies found various outcomes possibly linked to fab operations, but a clear association with the chemicals in the process was not found, possibly because of exposure assessment methodology. No study used a tiered assessment approach to identify similar exposure groups that incorporated manufacturing era, facility, fab environment, operation, job and level of exposure to individual hazardous agents. Further epidemiologic studies of fab workers are warranted with more refined exposure assessment methods incorporating both operation and job title and hazardous agents to examine the associations with cancer risk or mortality. Keywords: Chemical, Epidemiologic study, Fab operation, Retrospective exposure assessment, Semiconductor industry